Ketone Bodies Improve Human CD8+ Cytotoxic T-Cell Immune Response During COVID-19 Infection - Hirschberger, Simon; Gellert, Luca; Effinger, David; Muenchhoff, Maximilian; Herrmann, Markus; Briegel, Josef-Maria; Zwißler, Bernhard; Kreth, Simone (Frontiers in Medicine, 2022)
Severe COVID-19 is characterized by profound CD8+ T-cell dysfunction, which cannot be specifically treated to date. We here investigate whether metabolic CD8+ T-cell reprogramming by ketone bodies could be a promising strategy to overcome the immunoparalysis in COVID-19 patients. This approach was triggered by our recent pioneering study, which has provided evidence that CD8+ T-cell capacity in healthy subjects could be significantly empowered by a Ketogenic Diet. These improvements were achieved by immunometabolic rewiring towards oxidative phosphorylation. We here report similar strengthening of CD8+ T cells obtained from severely diseased COVID-19 patients: Ketone treatment induced elevated cytokine expression and enhanced cell lysis capacity. Metabolic analyses revealed upregulated mitochondrial respiratory chain activity, enabling both superior energy supply and higher mitochondrial reactive oxygen species signaling. These beneficial effects of ketones might represent evolutionary conserved mechanisms to strengthen human immunity. Our findings pave the road for metabolic treatment studies in COVID-19.